Lifestyle changes as a result of COVID‐19 containment measures: Bodyweight and glycemic control in patients with diabetes in the Japanese declaration of a state of emergency. Issue 9 (10th March 2021) - Tanaka, Nagaaki; Hamamoto, Yoshiyuki; Kurotobi, Yuri; Yamasaki, Yuji; Nakatani, Susumu; Matsubara, Miho; Haraguchi, Takuya; Yamaguchi, Yuko; Izumi, Kiyohiro; Fujita, Yuki; Kuwata, Hitoshi; Hyo, Takanori; et al.
Abstract: To clarify the association between lifestyle changes as a result of coronavirus disease 2019 containment measures and changes in metabolic and glycemic status in patients with diabetes, a cross‐sectional, single‐center, observation study was carried out. A self‐reported questionnaire was provided to ascertain the frequency of various lifestyle activities before and after the coronavirus disease 2019 containment measures in Japan. Among 463 patients, change in glycated hemoglobin was significantly associated with change in bodyweight. After stratification by age 65 years, binary logistic regression analysis showed that increased frequency of snack eating increased bodyweight (odds ratio 1.709, P  = 0.007) and glycated hemoglobin (odds ratio 1.420, P  = 0.025) in the younger group, whereas in the older patients, reduced walking activities resulted in weight gain (odds ratio 0.726, P  = 0.010). In conclusion, changes in eating behavior and physical activity increased bodyweight and reduced glycemic control among diabetes patients, but by different processes depending on age under the coronavirus disease 2019 containment measures in Japan. Abstract : We investigated lifestyle changes during the coronavirus disease 2019 containment measures, and its relationship with glycemic control and body weight change.